TI_GERICHTE 12.2004.185 vom 20. Dezember 2005 , contratto di pegno mobiliare - forma scritta - nullità - abuso di diritto ? - TI Tribunale d'appello (2005)
contratto di pegno mobiliare - forma scritta - nullità - abuso di diritto ?